Promoting Islam to non-Muslims: a study in da'wah bi'l-hikmah as a strategy - Babu Sahib, Hikmatullah; Yaacob, Asiah (Da'wah Academy, 2010)
Is there a specific strategy to promote Islam to non-Muslims? The fact is, Da‘wah approaches have been diverse and numerous. The stereotyping of one particular approach at the expense of other possible methods has resulted in lessening creativity in Da‘wah work. The present writers feel that Da‘wah approaches and methods need to be tailored to suit the needs of various localities taking full cognisance of the peculiar problems and prospects of each locality. This obviously calls for more accommodation with respect to adapting and adopting local customs and realities in promotion of Da‘wah activity. The writers firmly believe that owing to dissimilarities of people(s) with respect to their commitment to and practice of Islamic teachings Da‘wah work requires multilevel strategy using multiple fair means and thus feel that varying efforts made by various Da‘wah organisations need to be given due recognition since together they fill the gaps necessary to be filled in to reform the society. Addressing such a wide spectrum of people with diverse socio-politico-religious orientations is a great responsibility, which demands prudence, diligence and experience; the essence of Da‘wah bi ’l-╓ikmah.